2007
DOI: 10.5216/rpt.v34i1.2138
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Clínicos E Epidemiológicos Deum Foco De Sarna Sarcóptica Em Um Sistemaintensivo De Produção De Suínos Localizado No Município De Teresópolis-Go, Brasil

Abstract: A sarna sarcóptica continua sendo considerada um grande problema na suinocultura. O objetivo deste trabalho foi descrever as características clínicas e epidemiológicas de um foco de sarna sarcóptica em suínos mantidos em confinamento. O plantel de reprodutores era composto por 197 matrizes e 9 cachaços. Durante a visita seguiu-se um roteiro específico, anotando-se as informações relativas à epidemiologia da doença. Do plantel foram examinados individualmente 18 fêmeas e 5 machos, dos quais foram coletados rasp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
1
4
0
3
Order By: Relevance
“…suis infestation rates in pigs lower than and similar to that of this study were reported in industrial farms in Paraná (0.09%) and in Goiás (12.1%), respectively (Oliveira et al 2006, Silva et al 2002. Unlike the case records in Tanguá, Sobestiansky et al (2005) reported a high infestation rate (43%) on an industrial farm in Goiás, which already had a previous history of scabies.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…suis infestation rates in pigs lower than and similar to that of this study were reported in industrial farms in Paraná (0.09%) and in Goiás (12.1%), respectively (Oliveira et al 2006, Silva et al 2002. Unlike the case records in Tanguá, Sobestiansky et al (2005) reported a high infestation rate (43%) on an industrial farm in Goiás, which already had a previous history of scabies.…”
Section: Discussionsupporting
confidence: 73%
“…suis might have been even higher if the skin of the ear had been scraped to a greater intradermal depth, where most mites burrow, or if biological material had also been collected from other parts of the pigs' bodies. According to Sobestiansky et al (2005), scabies can pose problems in pig farming by lowering production rates because mite infested pigs reduce their feed intake, thus slowing down their growth and weight gains. Other evolutionary forms of arthropods were detected in this study, such as eggs characteristic of arthropods that could be S. scabiei var.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this investigation, evolutionary forms of this parasite were detected in 3.5% of the pigs, mainly in biological samples of animals from the finishing group. However, studies conducted at other pig farms in Brazil have reported the detection of higher infestation rates by this arthropod (12.1% to 43%) [17,51,52]. Sarcoptic mange can be a problem in pig raising and may reduce the animal production performance, given that pigs infested by the mite may suffer from severe itching, causing them to stop feeding and thus reduce their feed conversion efficiency [53].…”
Section: Discussionmentioning
confidence: 99%